Frequency and outcome of thrombocytopenia in neonates who are at risk of developing thrombocytopenia - a prospective observational study (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Thrombocytopenia is the commonest hematological abnormality encountered in the neonatal intensive care unit (NICU). This prospective, observational study was conducted among 78 consecutive at-risk neonates admitted in NICU, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from September 2016 to August 2017. Platelet count was measured in all at risk neonates at enrollment and less than 1,50,000/cmm was consiered as the cut off point for determining thrombocytopenia. Platelet count was measured every alternate day till discharge or normalisation of platelet count if the initial platelet count was low. If initial platelet count revealed normal, then the babies were followed up clinically if they develop any further risk condition for developing thrombocytopenia. During the period from enrollment to discharge, if any baby develops thrombocytopenia at any time then baby was defined as thrombocytopenic. Overall 39.7%patients found to be thrombocytopenic among 78 at-risk neonates. Pregnancy induced hypertension (PIH), neonatal sepsis and small for gestational age (SGA), intra uterine growth restriction(IUGR), prematurity, necrotizing enterocolitis (NEC) were significantly associated with thrombocytopenia. Sepsis and NEC were found to be independent risk factor for thrombocytopenia. Regarding outcome, length of hospital stay was significantly more in thrombocytopenic patients than non-thrombocytopenic patients. Death rate was also higher in thrombocytopenic patients in comparison to non-thrombocytopenic patients.BSMMU J 2022; 15(2): 115-120